Impact of Kovid-19 on Indian Society and Future Prospects in Higher Education: A Sociological Analysis: Covid-19 Ka Bhartiya Samaj Par Prabhav Evam Uchch Shiksha Me Bhavishya Ki Sambhavnayen: Ek Samajshastriya Vishleshan - Dr. Manoj Gupta; Dr. Nandan Singh (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2020)
Corona virus crisis affecting thousands and millions of people every day has affected the social life, politics, economy, religion, cultural life, and education of all the countries of the world including India in one way or the other. Methods are changing and new habits are being born. Thus our life and society are going through a great transformation and everywhere there is uncertainty and stagnation. The present study is a micro-level descriptive study of its impact on the Indian society and higher education system due to the global pandemic Corona (COVID-19) crisis in the country. The study has revealed the current scenario of Indian society and higher education, as well as the future possibilities in Indian society and higher education due to the Corona (Covid-19) crisis.